Levantamento de dados do açúcar VHP e boas práticas de fabricação para sua comercialização no mercado interno - Zacharias, Lucas Rakauskas (Universidade Federal de São Carlos, 2021)
The growth of the sugar-energy sector has increased over the years, and there is an increasing demand for more accessible and healthier foods. VHP sugar is one of the products most exported by Brazilian mills today, with the aim of serving as raw material for the production of refined sugar. The objective of the work is to carry out a survey of data on VHP sugar listing the best practices for its manufacture, in order to propose its commercialization in the domestic market.
Survey of data on VHP sugar and good manufacturing practices for its marketing in the domestic market
Keywords: Mercado; Açúcar; VHP; ANVISA; Sugar; Market; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE PRODUTOS DE ORIGEM VEGETAL